The Effect of Budget Participation on Managerial Performance with Organizational Commitment and Organizational Culture as Moderating Variables (Empirical Studies at the Economics Faculty, Gorontalo State University) - Nadira S. Sidik; Niswatin Niswatin; Nilawaty Yusuf (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
The role of budgetary participation in improving managerial performance occurs in the Higher Education environment. If not given the opportunity to determine the contents of the budget, it will cause dysfunctional behavior. The purpose of this study was to determine the effect of budgetary participation on managerial performance with organizational commitment and organizational culture as moderating variables. The type of method used in this study is a quantitative method with data collection techniques using a questionnaire survey. The number of respondents in this study were 62 respondents consisting of work unit leaders, lecturers, education staff and student organizations within the Faculty of Economics, State University of Gorontalo. The data analysis technique used is simple regression analysis and Moderated Regression Analysis (MRA) using IBM SPSS Version 25 Software. The finding of this study revealed that budgedtary participation positively but insignificantly affects managerial performance. Besides, organizational commitment and organizational culture strengthen the influence of budget participation on managerial performance.